MO405RISC FACTORS FOR CARDIAC SURGERY-ASSOCIATED ACUTE KIDNEY INJURY IN A TERTIARY REFERRAL HOSPITAL. (29th May 2021) - Lucas, Alvaro; Molina Andujar, Alicia; Quintana, Eduard; Piñeiro, Gaston; Poch, Esteban
Abstract: Background and Aims: cardiac surgery-associated acute kidney injury (CS-AKI) is a frequent complication that confers significant increase in morbility and mortality. It is still unclear how to identify patients at high risk to develop it, in order to apply to them early preventive strategies to avoid AKI. The study aimed to explore risk factors associated to CS-AKI. Method: to analyze the association between demographic, pre-operative and intraoperative variables with all grades-AKI, we collected baseline characteristics, type of surgery, aortic time of clampage and extracorporeal circulation time, hemodinamic variables during surgery, Euroscore II, Clevelant Clinic Score and Leicester cardiosurgery score. The post-operative variables included monitorization of the first 24 h in the Intensive Care Units (ICU), consistent in: use of vasoactive drugs, total diuresis, use of furosemide, need of transfusions and need and duration of renal replacement therapy (RRT). Creatinine was collected for all the admision days in order to calculate the incidence of AKI. Also mortality and need of RRT at 30 th day was assessed. The inclusion criteria were: patients over 18 years old who underwent cardiac surgery with extracorporeal circulation. Only valve substitution (VS), Coronary Artery Bypass Graft (CABG) or a combination of both procedures (not including endocarditis surgery) were included. Patients who were already in dialysis or suffered an AKI just before the surgery were not included in the study. Results: we included 130 patients who underwent heart surgery intervention in Hospital Clínic de Barcelona from 1 st January to 31 st March 2015. 61, 5% were men and the majority of them was 60 - 75 years old (46.9%), with hypertension (80.8%), without diabetes (68.5%), with stage 2-Chronic Kidney Disease (53.1%). Main surgical procedure was CABG (50.8%), followed by valve substitution (36.1%) and combination of both (13.1%). 73, 1% of the procedures were done electively and 26.9% urgently. Out of the 130 patients, 60 (46.2%) suffered an AKI (36 AKIN 1, 16 AKIN 2 and 8 AKIN3). The majority of the episodes (55.2%) started between 24 and 48 hours after the intervention and 7 patients required RRT. AKI was not associated with mortality or need of renal replacement therapy at 30 days (OR 1.853, p= 0.397). Regarding risk factors for CS-AKI, basal eGFR <60 ml/min, history of hypertension, age and the clevelant/leicester and euroscore were preoperative risk factors associated with CS-AKI in our cohort (OR 5.571 p=<0.001; OR 2.621 p=0.043; OR 1.036 p<0.001; OR 1.453 p=0.045; OR 1.062 p<0.001; OR 1.351 p=0.006 respectively). Leicester cardiosurgery score >30 was the score who showed the best association with AKI (OR 5.167, p<0.001). Intraoperative significant risk factors that were identified were: ischaemia time over 70 minutes (OR 2.876, p=0.004), and the need to use phenylephrine (3.064, p=0.015); whereas the need to use nitroglycerin was identified as a protector (OR 0.441, p=0.031). Conclusion: previous eGFR<60 ml/min, age, hypertension, use of phenylephrine during surgery and long ischaemia time are the main factors associated with CS-AKI. Scores like Leicester score can help physicians to identify people at risk and apply preventive strategies.